Plasma angiotensin II, predisposition to hypertension, and left ventricular size in healthy young adults - Harrap, S B; Dominiczak, A F; Fraser, R; Lever, A F; Morton, J J; Foy, C J; Watt, G C (Circulation (New York, N.Y.), 1996)
We studied the correlates of left ventricular mass (LVM) in 84 healthy young adults aged 16 to 24 years from the general population. Subjects were selected according to predisposition to hypertension into four groups with either high or low personal blood pressures and either high or low parental blood pressures. LVM was measured by echocardiography, and measurements of blood pressure, heart rate, body dimensions, and plasma concentrations of components of the renin-angiotensin system were made under resting conditions. LVM was similar in individuals predisposed to hypertension (high personal and parental blood pressures) and those with contrasting predisposition (low personal and parental pressures). Regression analysis of the combined groups showed that LVM correlated closely with body size, particularly lean body mass (r=.69, P<.0001) and systolic (r=.35, P<.0001) but not diastolic blood pressure. Plasma angiotensin II (r=.39, P<.0001), renin (r=.302, P<.01), and angiotensin-converting enzyme (r=.22, P<.05) showed significant correlation with LVM. Multiple regression analysis revealed that plasma angiotensin II was the most important component of the renin-angiotensin system and that its effect was independent of systolic blood pressure and body size. These findings provide evidence in humans that angiotensin II exerts a direct on myocardial size. This association may have important implications for the complications and treatment of left ventricular hypertrophy.